Hybrid Learning Model in Post-Pandemic Education: Lecturers Attitude in Indonesian and Uzbekistan Higher Education - Rum, Eka Prabawati; Baso, Farisha Andi; Musoyeva, Aziza (Aptisi Transactions On Technopreneurship (ATT), 2025)
Since hybrid learning has grown in popularity in the post COVID-19 era, regular evaluation is critical to improving the quality of hybrid learning in higher education. Considering the issue, the current study seeks to explore how the lecturers both universities, Indonesia and Uzbekistan, perceive hybrid learning model and how they put their perception into the classroom practice. This study employs sequential explanatory research and uses atlas.ti9 to analyze the necessary data. The results indicate substantial differences in the way lecturers put their perception of hybrid learning into the classroom. The differences are categorized into two types of lectures, namely highly concerned of hybrid learning and lowly concerned of hybrid learning. It is identifiable that the more lecturers perceive positive attitude of hybrid learning model the more lecturers well-adopted of hybrid learning model into the classroom practice. This study offers beneficial insights for higher education stakeholders to improve the quality of hybrid learning in university settings. This research distinguishes itself by focusing on a comparative analysis of lecturers attitudes from two different cultural and educational systems, Indonesia and Uzbekistan. While prior studies have explored hybrid learning models in individual contexts, few have examined their cross-cultural adoption and practical implementation. This comparative approach provides novel insights into how hybrid learning can be adapted to diverse educational landscapes, contributing both to theory and practice.